CLINICAL MANIFESTATIONS OF LACTOSE INTOLERANCE AND RELATIONSHIP WITH A1 AND A2 BETA CASEIN MILK - Eduarda Silva Souza, Maria; Oliveira Facin Souza, Dienypher; Costa Lopes, Marden; Figueiredo Santos, Vanilde; Paiva dos Santos Rocha, Silvânia; Siega Nepomuceno, Matheus; Julliana Costa Diniz, Héllen; Sérgio David de Castro, Paulo; Joyce de Freitas Zacarias Martello, Khetene; Martins Pereira Mesquita, Maria Thereza; Silva Pereira, Alessandra; Antunes Aquino Cardoso Gonçalves, Sueli; et al. (Health and Society, 2026)
The aim was to understand the clinical manifestations of lactose intolerance and its relationship with A1 and A2 Beta-Casein milk. This study sought to examine the clinical manifestations of lactose intolerance and its possible relationship with the consumption of milk containing the A1 and A2 variants of Beta-Casein. An integrative literature review was conducted, analyzing articles retrieved from secondary databases including the Virtual Health Library, Latin American and Caribbean Health Sciences Literature, Scientific Electronic Library Online, and the Online System for Search and Analysis of Medical Literature, based on descriptors used in health sciences. The selected studies consistently showed that the clinical manifestations of lactose intolerance (LI) are predominantly gastrointestinal. The most frequently reported symptoms include: abdominal pain and cramps (present in 92% of the studies); abdominal bloating and distension (present in 88% of the studies); excessive flatulence (present in 80% of the studies); and diarrhea (present in 64% of the studies). The findings indicate that while LI is a carbohydrate maldigestion condition, sensitivity to A1 beta-casein may be a complicating factor or a parallel cause of discomfort in individuals who avoid milk. The results reinforce that lactose intolerance primarily manifests through classic gastrointestinal symptoms, such as abdominal pain, bloating, flatulence, and diarrhea, due to low lactase enzyme activity.